PENGARUH GOVERNANCE STRUCTURE, GOVERNANCE PROCESS DAN GOVERNANCE OUTCOME TERHADAP OPERATIONAL RISK PERBANKAN DI INDONESIA - kundy, ruth; Handayani, Susi (Jurnal Akuntansi AKUNESA, 2020)
This study aims to examine the effect of Governance Structure, Governance Process and Governance Outcome on Banking Operational Risk in Indonesia. The research sample is all conventional commercial banks on the Indonesia Stock Exchange the periode 2014 until 2017. The sample obtained was 80 conventional banks. The analysis technique used in this study is multiple linear regression with using IBM SPSS Statistics program 23. The results of the study show that Governance Structure and Governance Outcome have no effect, while the Governance Process influences operational risk. This is because the Governance Process which is proxied by the amount of training has a significant impact in reducing operational risk, because training can increase the accuracy and independence of a committee in detecting risks that can harm the company.